2024
DOI: 10.1186/s12886-024-03414-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative visual outcomes of the first versus second eye following small-incision lenticule extraction (SMILE)

Anzhen Li,
Xiaowei Yang,
Wei Wang
et al.

Abstract: Background This study aimed to compare the visual outcomes of the first operated eyes with those of the second operated eyes following small-incision lenticule extraction (SMILE). Methods A total of 202 patients (404 eyes) underwent SMILE using the tear film mark centration method for myopia and myopic astigmatism correction. Baseline characteristics, objective optical quality, decentered displacement, induced corneal aberrations, and modulation tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Decentration was related to a larger induction of HOAs in SMILE 30 . In a previous study comparing binocular SMILE data, more centered eyes showed better clinical outcomes in terms of HOAs 31 . Our results showed that CentraLign of VISUMAX 800 significantly helped the operators align the center of the optical zone and improved the clinical outcomes in HOAs compared to VISUMAX 500 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Decentration was related to a larger induction of HOAs in SMILE 30 . In a previous study comparing binocular SMILE data, more centered eyes showed better clinical outcomes in terms of HOAs 31 . Our results showed that CentraLign of VISUMAX 800 significantly helped the operators align the center of the optical zone and improved the clinical outcomes in HOAs compared to VISUMAX 500 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 76%